The comparison of different methods of determining the rock density from gravity data - ZAHOREC, Pavol; MIKUŠKA, Ján; PAPČO, Juraj; PAŠTEKA, Roman (Contributions to Geophysics and Geodesy, 2023)
We focus on two methods of determining the density of the rock environment based on gravimetric measurements. The first method, a combined underground-surface approach, relies on recent measurements made at pairs of points along the vertical. One point is located in accessible underground spaces, like tunnels, mine workings, or caves, while the other is on the Earth's surface. The second, surface method, is solely based on the analysis of the Gravimetric Database of the Slovak Republic. Both methods are based on the proportionality between free-air anomalies and the gravitational effect of topographic masses, calculated for unit density. We compare the respective outputs of both methods and attempt to understand the existing differences between them. We also confront the density estimates in question with one of the two existing density maps of Slovakia compiled from density measurements on rock samples. Across a total of 14 measured locations, we observe a relatively wide spectrum of values on the agreement-disagreement scale, ranging from close similarity to relatively significant differences.